Rabbit antibody responses to experimental infestation with Dermatobia hominis. - De Lello, E.; Boulard, C. (Wiley, 1990)
The three larval stages of Dermatobia hominis (Linnaeus) have been evaluated for their immunogenicity by ELISA and immunodiffusion (ID) using sera from experimentally infested rabbits. During a primary infestation, first instar D. hominis were found to cause most reaction and allowed the earliest diagnosis by ELISA. An inhibition of the antibody response against second and third instars was observed. The inhibition disappeared after departure of the larvae from the host. In experimentally immunized hosts the antibody response, following challenge, was highest against second and third instar antigens. Antibody remained elevated during the infestation but fell immediately after the larvae had left the host.
Keywords: antigen; animal; animal disease; antibody production; enzyme linked immunosorbent assay; fly; immunodiffusion; immunology; kinetics; larva; myiasis; rabbit; Animal; Antibody Formation; Antigens; Diptera; Enzyme-Linked Immunosorbent Assay; Immunodiffusion; Kinetics; Larva; Myiasis; Rabbits; Support, Non-U.S. Gov't